Pre-emptive versus preventive analgesia for postoperative pain: a systematic review and meta-analysis - Aida Rosita Tantri; Riyadh Firdaus; Hansen Angkasa; Ahmad Pasha Natanegara; Muhammad A. I. Maulana (Faculty of Medicine, Universitas Trisakti, 2023)
BackgroundPostoperative pain is a type of nociceptive pain that originates from tissue damage due to trauma caused by surgery. Pre-emptive analgesia is treatment that starts before surgery, to prevent or reduce the establishment of sensitization of dorsal horn neurons caused by tissue injury, the sensitized neurons being supposed to amplify postoperative pain. Pre-emptive analgesia consists of administering analgesic medication before tissue injury, that is, before the reception, transmission, modulation, and nociception of the aggressive stimulus, aiming to prevent hyperalgesia. This review aims to compare the efficacy of pre-emptive analgesia and preventive analgesia in postoperative pain. MethodsArticle searching was done on five databases (PubMed, ProQuest, Scopus, ScienceDirect, ClinicalKey). Hand-searching was also done to find additional articles. We have only included double-blind, randomized, controlled trials (RCT). A total of fifteen articles were included and all were RCT studies comparing pre-emptive analgesia with preventive analgesia. The quality of the included studies was evaluated with Cochrane risk-of-bias assessment tools. Quantitative analysis was performed by Review Manager 5.4. ResultsFifteen studies comprising 830 subjects were included in this study. Our analysis revealed that pre-emptive analgesia significantly improved visual analog scale (VAS)/numeric rating scale (NRS)/verbal rating scale (VRS) 4 hours postoperatively [mean difference (MD) = -0.25, 95% CI: [- 0.49, -0.02]; I2 = 94%]. Unfortunately, pain scoring at 6, 12 and 24 hours after surgery did not differ significantly between pre-emptive and preventive analgesia. Duration of analgesia was comparable between the two groups. Time to rescue analgesics was similar between the two groups, but the pre-emptive group was associated with less analgesic consumption postoperatively than the preventive group. ConclusionPre-emptive analgesia provided better pain relief than preventive analgesia during the short term. Time to rescue analgesics is comparable between both groups, but pre-emptive analgesia is associated with lower amounts of rescue analgesics postoperatively.